PERSEPSI GURU TERHADAP KEBERAGAMAN AGAMA ANAK USIA DINI DI TK - Jessica, Agustina; Ali, Muhamad; Amalia, Annisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The perception of a good teacher will certainly have a positive effect in supporting the implementation of learning in schools, besides that the perception of the teacher is also important for us to know because the perception of a good teacher will also have an impact on the formation of children's self, because in it there is a personal value that can be seen from how an educator present himself and be an example to his students. A teacher must also have self-respect, honesty, fairness and good manners as well. This study aims to describe teachers' perceptions of the religious diversity of early childhood in the kindergarten. The research method used is a descriptive method with a qualitative research form. The data sources in this study were 2 class teachers in the kindergarten. Data collection techniques used in this study were observation, interviews and documentation. Data analysis was carried out namely data collection, data reduction, data presentation, and drawing conclusions. Techniques for checking the validity of the data are triangulation and member checks. The results of this study indicate that the teacher's perception of the religious diversity of early childhood in kindergarten through the cognitive, affective and conative components is very good. This can be seen from the knowledge that teachers have regarding the diversity of children's religions, the way teachers behave towards children and the actions that teachers take in learning in class. The conclusion in this study is that the teacher's perception of the religious diversity of early childhood in kindergarten is quite good, but there are still several components that the teacher needs to optimize again.